2004
DOI: 10.1097/00001756-200403220-00001
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of a glutamine transporter SNAT3 is a marker of malignant gliomas

Abstract: Glutamine (Gln) is a growth determinant in neoplastic tissues. We analysed by RT-PCR the expression of mRNAs coding for the human variants of Gln transporters: ASCT2 (system ASC), SNAT1 [ATA1] (system A), SNAT3 [SN1] and SNAT5 [SN2] (system N), in samples of human malignant gliomas WHO grades III/IV (anaplastic astrocytoma and glioblastoma), glioma-derived cell cultures, brain metastases from peripheral organs, and control brain tissue. SNAT3 mRNA showed a 3-5 times stronger expression in gliomas than in metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 21 publications
1
43
0
1
Order By: Relevance
“…In the present study, we demonstrated a significant increase in ASCT2 mRNA expression in a stepwise pattern in parallel to the increase of malignancy among astrocytomas, confirming previous data. 25 The involvement of ASCT2 in cancer cell proliferation has been confirmed in vitro assay with C6 mouse glioma cell line, 26 and cell line derived from human neuroblastoma. 27 Studies have demonstrated that ASCT2 expression Curves show sensitivity and specificity of ASCT2 expression level in all grades of astrocytomas compared to non--neoplastic brain tissues while LAT1 expression levels show better sensitivity and specificity on more malignant grades of astrocytomas (grade III and IV).…”
Section: ■ Discussionmentioning
confidence: 85%
“…In the present study, we demonstrated a significant increase in ASCT2 mRNA expression in a stepwise pattern in parallel to the increase of malignancy among astrocytomas, confirming previous data. 25 The involvement of ASCT2 in cancer cell proliferation has been confirmed in vitro assay with C6 mouse glioma cell line, 26 and cell line derived from human neuroblastoma. 27 Studies have demonstrated that ASCT2 expression Curves show sensitivity and specificity of ASCT2 expression level in all grades of astrocytomas compared to non--neoplastic brain tissues while LAT1 expression levels show better sensitivity and specificity on more malignant grades of astrocytomas (grade III and IV).…”
Section: ■ Discussionmentioning
confidence: 85%
“…With the ongoing development in biological research, key molecules involved in several pathways may aid in diagnosing and predicting future recurrence and prognosis [11][12][13][14]. Because of their potential roles in nutrients or energy metabolism of tumor cells, amino acid transporters have become the foci for malignant transformation of mammalian cells, including system A amino acid transporter [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Three distinct transporter proteins have been identified that are responsible for system A transport activity in mammalian cells [22]. The three transporters are known as amino acid transporter A (ATA)1, ATA2, and ATA3 [18,23]. These transporters belong to the solute-linked carrier family SLC38 and exhibit differential tissue expression patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…64,65 As glucose levels in the cell decline, glycosylation is inhibited and plasma membrane levels of growth factor receptors and transporters are reduced, 66 including the glutamine importer ASCT2. Glutamine importers are upregulated in a number of cancer cells lines 67,68 possibly through autocrine growth factor signaling, 69 leading to a glutamine "addiction" phenotype. 11 Loss of glutamine influx may inhibit glutathione, nucleotide, and amino acid synthesis resulting in the induction of autophagy or apoptosis.…”
Section: Discussionmentioning
confidence: 99%